2021
DOI: 10.1038/s41598-021-82020-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography in an “oyster” shell provides first insights into the genetic structure of an extinct Ostrea edulis population

Abstract: The historical phylogeography of Ostrea edulis was successfully depicted in its native range for the first time using ancient DNA methods on dry shells from museum collections. This research reconstructed the historical population structure of the European flat oyster across Europe in the 1870s—including the now extinct population in the Wadden Sea. In total, four haplogroups were identified with one haplogroup having a patchy distribution from the North Sea to the Atlantic coast of France. This irregular dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 65 publications
3
8
0
Order By: Relevance
“…Furthermore, phenol-chloroform increases costs (by ~19.5% and ~57% compared to ‘modified Yang’ and ‘modified Dabney’, respectively, in our conditions), hands-on time, user risk (manipulation/storage of toxic chemicals) and equipment requisites (e.g., chemical hood). As in Gamba et al [ 22 ], we found no practical differences in implementing either ‘modified Yang’ or ‘modified Dabney’: the latter, previously applied to ancient shells in e.g., Hayer et al [ 41 ], Psonis et al [ 51 ], Sullivan et al [ 52 ], Walton et al [ 44 ], was nevertheless ~31% cheaper.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, phenol-chloroform increases costs (by ~19.5% and ~57% compared to ‘modified Yang’ and ‘modified Dabney’, respectively, in our conditions), hands-on time, user risk (manipulation/storage of toxic chemicals) and equipment requisites (e.g., chemical hood). As in Gamba et al [ 22 ], we found no practical differences in implementing either ‘modified Yang’ or ‘modified Dabney’: the latter, previously applied to ancient shells in e.g., Hayer et al [ 41 ], Psonis et al [ 51 ], Sullivan et al [ 52 ], Walton et al [ 44 ], was nevertheless ~31% cheaper.…”
Section: Discussionsupporting
confidence: 56%
“…Until now, methodological optimization and standards for ethical research have mostly focused on bones and teeth. Meanwhile, mollusc shells have emerged as promising substrates for DNA analyses (e.g., [38][39][40][41][42][43][44][45]) of samples as old as 100,000 years Before Present (yBP; [46]; reviewed in Martin et al [47]). In a similar way to morphological, sclerochronological, sclerochemical, or dating methods commonly applied to ancient mollusc shells from shell middens, refuse dumps, sediment cores or historical collections, aDNA analysis has the potential to provide invaluable evolutionary, ecological and archaeological insights into the impact of climate and environmental changes, as well as into past human activities and resource management strategies: subsistence systems, mobility, migration, exchange networks, aquaculture, production of tools and symbolic artefacts (reviewed in Coutellec [48] and Thomas [49,50]).…”
Section: Introductionmentioning
confidence: 99%
“…This rich archival source has already shed light on historical distributions of haplotypes (e.g. Hayer et al, 2021) and illustrates the potential for combining contemporary and historic population genomics to better understand the factors contributing to current phylogeographic patterns and to tell us what contemporary samples never can: what genetic variation has been lost. Access to entire communities in a microcosm further highlights the potential for detection of genomic community-scale responses through time (e.g.…”
Section: Cp In the Anthrop O Cenementioning
confidence: 99%
“…Since changing oyster supplies historically could equate with multiple sources for the archaeological assemblages, correctly assigning a historical fishery provenance may ultimately depend on genetic or other attributes of the shell itself (e.g. Hayer et al, 2021;Mouchi et al, 2018Mouchi et al, , 2021.…”
Section: Oyster Fisheries Provenancementioning
confidence: 99%